Let-7a-5p regulates the inflammatory response in chronic rhinosinusitis with nasal polyps - Jianwei Zhang; Lei Han; Feng Chen (BMC, 2021)
Abstract Background Let-7a-5p is demonstrated to be a tumor inhibitor in nasopharyngeal carcinoma. However, the role of let-7a-5p in chronic rhinosinusitis with nasal polyps (CRSwNP) has not been reported. This study is designed to determine the pattern of expression and role of let-7a-5p in CRSwNP. Methods The expression level of let-7a-5p, TNF-α, IL-1β, and IL-6 in CRSwNP tissues and cells were detected by RT-qPCR. Western blot assay was carried out to measure the protein expression of the Ras-MAPK pathway. Dual luciferase reporter assay and RNA pull-down assay were used to explore the relationship between let-7a-5p and IL-6. Results Let-7a-5p was significantly downregulated in CRSwNP tissues and cells. Moreover, the mRNA expression of TNF-α, IL-1β and IL-6 was increased in CRSwNP tissues, while let-7a-5p mimic inhibited the expression of TNF-α, IL-1β and IL-6. Besides that, let-7a-5p was negatively correlated with TNF-α, IL-1β and IL-6 in CRSwNP tissues. In our study, IL-6 was found to be a target gene of let-7a-5p. Additionally, let-7-5p mimic obviously reduced the protein levels of Ras, p-Raf1, p-MEK1 and p-ERK1/2, while IL-6 overexpression destroyed the inhibitory effect of let-7a-5p on the Ras-MAPK pathway in CRSwNP. Conclusion We demonstrated that let-7a-5p/IL-6 interaction regulated the inflammatory response through the Ras-MAPK pathway in CRSwNP.